The influence of dietary antioxidant on ovarian eggs and levels of vitamin E, C, A, astaxanthin, Î²-carotene and oxidative stres in tissues of Astacus leptodactylus (Eschscholtz) during reproduction - Barim-Oz, O.; Sahin, H. (Cellular and Molecular Biology, 2016)
The experiment was conducted to determine the most effective antioxidant (among the vitamin E (VE), vitamin C (VC), vitamin A (VA), astaxanthine (AX), Î²-carotene (Î²C)) on the ovarian egg number and size, level of VE, VC, VA, AX, Î²C and oxidative stress (as malondialdehyde (MDA)) in the hepatopancreas, ovarian, gills and muscle tissue during ovarian development of Astacus leptodactylus. One control (C) and five experimental diets (EE, EC, EA, EAX and EÎ²C) were prepared. The EE, EC, EA, EAX and EÎ²C groups were formed by added 150 mg kg-1 VE, 200 mg kg-1 VC, 240 mg kg-1 VA, 200 mg kg-1 AX and 200 mg kg-1 Î²C to diet C, respectively. At the end of the experiment found that the dietary antioxidants increased ovarian egg number and size and reduced the level of MDA in the tissues. Ovarian egg number and size were highest in the EE and EAX diet groups in the comparison to control (p<0.001). The level of MDA in the tissues was lowest in the EAX diet group in the comparison to control (p<0.001). The highest levels of VE, VC, VA, AX and Î²C were found in the hepatopancreas and ovarian compared with muscle and gills. The highest level of MDA also was determined in the ovarian according to other tissues. In conclusion, the VE and AX in broodstock diets were the most effective antioxidants on the ovarian egg number and size of A. leptodactylus.